Step by step transfusion timeline and its challenges in trauma: A retrospective study in a level one trauma center. (4th July 2022) - Boye, Matthieu; Py, Nicolas; Libert, Nicolas; Chrisment, Anne; Pissot, Mathieu; Dedome, Emmanuel; Martinaud, Christophe; Ausset, Sylvain; Boutonnet, Mathieu; De Rudnicki, Stéphane; Pasquier, Pierre; Martinez, Thibault
Abstract: Background: Hemorrhagic shock is the leading cause of preventable early death in trauma patients. Transfusion management is guided by international guidelines promoting early and aggressive transfusion strategies. This study aimed to describe transfusion timelines in a trauma center and to identify key points to performing early and efficient transfusions. Methods: This is a monocentric retrospective study of 108 severe trauma patients, transfused within the first 48 h and hospitalized in an intensive care unit between January 2017 and May 2019. RESULTS: One hundred and eight patients were transfused with 1250 labile blood products. Half of these labile blood products were transfused within 3 h of admission and consumed by 26 patients requiring massive transfusion (≥4 red blood cells [RBC] within 1 h). Among these, the median delay from patient's admission to labile blood products prescription was −11 min (−34 to −1); from admission to delivery of labile blood products was 1 min (−20 to 16); and from admission to first transfusion was 20 min (7–37) for RBC, 26 min (13–38) for plasma, and 72 min (51–103) for platelet concentrates. The anticipated prescription of labile blood products and the use of massive transfusion packs and lyophilized plasma units were associated with earlier achievement of high transfusion ratios. Conclusion: This study provides detailed data on the transfusion timelines and composition, from prescription to initial transfusion. Transfusion anticipation, use of preconditioned transfusion packs including platelets, and lyophilized plasma allow rapid and high‐ratio transfusion practices in severe trauma patients.